El difícil choque entre el Este y el Oeste en el nacer del nacionalismo gallego .......... 101 - Filipowicz-Rudek, Maria (Pensées orientale et occidentale : influences et complémentarité II, 2021)
THE DIFFICULT CLASH BETWEEN EAST AND WEST AT THE BIRTH OF GALICIAN NATIONALISMSpain from the historical point of view remains, without a doubt, one of the key sceneries in medieval Europe where the East and the West intersected in a fruitful way. The prominence of the Jewish people in this process played an unquestionable part in it. In this context the anti-Semitic component in the construction of Galician nationalism is interesting, while creating the founding myth contrasts the West and the East. In the background of this great cultural creation, full of consequences, we may glimpse the absent history of Galicia, the small demos of the western end of the Roman Finisterrae.